Management Structures and Processes to Optimise Motivation and Engagement amongst Casual Academic Staff Working in Fully Online Programs - Morey, Valerie Jean (Curtin University, 2021)
The thesis presents a case study that investigated how levels of motivation and engagement are experienced by casual academic staff working in one fully online initial teacher education program in Australia. The study was framed using the Job Demands-Resources (JD-R) theory and model and participants’ levels of motivation and engagement were measured using the Utrecht Work Engagement Scale (UWES). Recommendations are made for organisational structures and processes to optimise motivation and engagement of casual academics.